HUBUNGAN JUMLAH ANGGOTA DAN LAMA TERBENTUKNYA KELOMPOK PETERNAK DENGAN MODAL SOSIAL PETERNAK KAMBING PE DI KECAMATAN KALIGESING PURWOREJO - Inayatillah, Khoerotunnisa; Muatip, Krismiwati; Purwaningsih, Hermin (ANGON: Journal of Animal Science and Technology, 2024)
The number of members and the length of time the PE Ras Kaligesing Goat Farming group was formed in Kaligesing District has an important role because it influences the social capital of the breeder group. The aims of this study were (1) the number of members and how long the Goat Breeders Group was formed PE. (2) How is the social capital of the PE goat breeder group in Kaligesing. (3) How is the relationship the number of members and the length of time the group was formed with the social capital of PE Goat Breeders in Kaligesing. This study uses a survey method. Determination of the research area is carried out using purposive sampling method in Kaligesing District which is the center of livestock development PE Goat. Kaligesing District has 21 villages, 15% of which are sampled villages. Village selection randomly carried out as many as 3 villages from the number of villages that have PE Goat Breeders groups, Pandanrejo Village, Donorejo Village and Tawangsari Village were selected. The number of respondents is calculated using slovin formula with a margin of error of 10%, obtained by 70 respondents. Selection of respondents taken at random. The analytical method used is descriptive analysis and rank correlation analysis spearmen. The results showed that the number of goat breeders in the Kaligesing District members in the moderate category with an average number of 17.57, the length of time the group was formed in the category long enough and the social capital of the breeder group is in the quite high category. Based on the analysis results spearman rank, the number of members and the length of time the breeder group was formed is quite low with capital social.